The Good Place. The complete second season [videorecording (DVD)] - O'Donnell, Trent; Goddard, Drew, 1975-; Bell, Kristen, 1980-; Harper, William Jackson, 1980-; Jamil, Jameela, 1986- (Shout! Factory, 2018)
After her death, a woman wakes up in the Good Place, an afterlife town inhabited by the people who have led righteous lives, but the problem is that she gets sent there by mistake.